2017
DOI: 10.1016/j.ijpsycho.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of startle reactivity and affect modified startle

Abstract: Startle reflex and affect-modified startle reflex are used as indicators of defensive reactivity and emotional processing, respectively. The present study investigated the heritability of both the startle blink reflex and affect modification of this reflex in a community sample of 772 twins ages 14–15 years old. Subjects were shown affective picture slides falling in three valence categories: negative, positive and neutral; crossed with two arousal categories: high arousal and low arousal. Some of these slides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…The current findings are in line with those of two previous twin studies (Anokhin et al, ; Dhamija et al, ), which concluded that a common pathway model with a single set of genetic and environmental factors was the driving force behind startle response to neutral, positive, and negative affective stimuli. Another study (Vaidyanathan et al, ) found that overall raw SR, but not modulated startle, was moderately heritable.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The current findings are in line with those of two previous twin studies (Anokhin et al, ; Dhamija et al, ), which concluded that a common pathway model with a single set of genetic and environmental factors was the driving force behind startle response to neutral, positive, and negative affective stimuli. Another study (Vaidyanathan et al, ) found that overall raw SR, but not modulated startle, was moderately heritable.…”
Section: Discussionsupporting
confidence: 93%
“…Some aspects of the SR have been found to be heritable; for a thorough review, see Savage, Sawyers, Roberson-Nay, and Hettema (2017). Briefly, studies have found the overall SR (not FPS) to have a heritability of 37-67% (Anokhin, Golosheykin, & Heath, 2007;Dhamija, Tuvblad, Dawson, Raine, & Baker, 2017;Vaidyanathan, Malone, Miller, McGue, & Iacono, 2014). These same studies, using negative/positive affective imagery to alter SR, found no genetic contribution to the affective modulation of startle in humans.…”
Section: Savage Et Almentioning
confidence: 99%
See 3 more Smart Citations